System‐level assertions: approach for electronic system‐level verification. Issue 3 (1st May 2015) - Sohofi, Hassan; Navabi, Zainalabedin
Abstract : As design of digital systems become more complex and more transistors are incorporated into a single chip, design and verification methodologies moves into higher levels. Now that design at the register transfer level (RTL) has reached its maturity, the focus is shifting to electronic system level (ESL) design tools, languages and methodologies. At the centre of this and perhaps the most challenging are verification methods and tools to use for verifying designs at the ESL. This study presents a new concept of system‐level assertions for ESL verification. It also demonstrates an environment for functionally verifying system‐level designs using these system‐level assertions. The proposed environment adapts existing EDA simulation tools, which are mainly used for RTL design and verification, and utilises them for system‐level verification. In this environment, designs are modelled in SystemC‐transaction level modelling 2.0, and assertions are written in SystemVerilog. Design and verification parts are connected together using SystemVerilog Direct Programming Interface mechanism, and designs that are described in SystemC are verified against system‐level assertions in the course of SystemVerilog simulation.